Status Pewarisan Transeksusal dalam Perspektif Hukum Waris Adat Kecamatan Labuhan Haji Kabupaten Aceh Selatan - Kresia Kresia; Muhammad Riyan Wahyuda; Daryll Alessandro Indratmoko (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Law is a regulation that regulates and enforces society, containing regulations or prohibitions on actions within a state order established by authorized institutions. Basically, law is formed because of an event, meaning that law follows changes in society. Indonesia is a country based on Pancasila, which has very diverse ethnicities, religions and races. This is what causes Indonesia to have diverse customs, which means that customary law in Indonesia has diversity. Customary inheritance law in Indonesia has three inheritance distribution systems, namely patrilineal customary inheritance, matrilineal customary inheritance, and parental customary inheritance. Patrilineal traditional inheritance is inheritance drawn from the father's lineage, traditional matrilineal inheritance is inheritance drawn from the mother's lineage, and parental inheritance is inheritance drawn from the second lineage.